The Factors Affected m-Services Adoption in Airports - Burhanuddin Hanantyo; Bambang Setiawan; Izzat Aulia Akbar (Universitas Medan Area, 2022)
This research focus on the factors which affected m-Services utilization in airport from airport’s functionaries point of view. Also, the background of this research is related to some former researches which defined some models that may increase the exertion of electronic mobile based service application (m-Services) such as: TAM, UTAUT, and UTAUT2. However, the former literature reviews only elucidate the factors which affect the increasing of m-Services or mobile technologies/ self service technology exertion from customer point of view. While, there are less of them apprising the factors affected m-Services adoption from airport’s functionaries point of view. The purpose of this study is fulfilling the lack in the literature review by apprising the study towards airport’s functionaries point of view. To reach the purpose of the study, this study applies literature review method. The literature review’s source of this study is originated from some international journals which discuss the factors of airport’s functionaries side. The result of this study are the Explanation of the factors affected m-Service adoption or mobile technologies/ self-services technology from airport’s functionaries point of view and the development of conceptual model related to the factors affected m-Services adoption from airport’s function perspective.